Data driven modelling of permafrost induced geomorphological hazard - Elia, Letizia <1993> (Alma Mater Studiorum - Università di Bologna, 2024)
My thesis dives into a relevant scientific problem which involves two aspects. The first corresponds to the need to employ data-driven solutions to cryospheric hazards in high-latitude landscapes. This is due to the limited data historically collected across such landscapes and it links to the second aspect: a contribution in the form of mapping and sharing results with the whole community. In fact, I have been involved in mapping cryospheric processes such as thaw slumps (TS), retrogressive thaw slumps (RTS), active layer detachments (ALD), and thermo-erosion gullies (TEG), and developing susceptibility models for each one of them and their potential combination. As a sub-theme to my research, I have also explored whether immovable infrastructure such as cultural heritage sites may be subjected to any of the processes mentioned above. In fact, if that is the case, the memories and value associated to such heritage may be lost, especially because climate projections are expected to further promote permafrost degradation across the whole Arctic and peri-Arctic regions. The thesis is divided into three main components, each corresponding to one of the main experiments I have carried out. In terms of study areas, I have addressed analogous problems and research applications in Alaskan and Norwegian areas.